'Changing the way we do child protection': The implementation of Signs of Safety® within the Western Australia Department for Child Protection and Family Support. (January 2015) - Salveron, Mary; Bromfield, Leah; Kirika, Clara; Simmons, Jane; Murphy, Terry; Turnell, Andrew
Abstract: Objective: This paper describes a six-year large scale implementation of the Signs of Safety practise framework in a complex statutory child protection context in Western Australia. The case study documents both the practitioner-led and organisational-led implementation journey as part of the State's child protection system reform drawing on Roger's diffusion of innovation theory and Fixsen's five stage implementation model as conceptual frameworks, and highlighting the key facilitators and barriers. Methods: The study is a collaboration between researchers investigating the impact and use of Signs of Safety in Western Australia who contributed the theoretical perspectives and analysis; and key personnel from the Department responsible for implementation who contributed documents, manuals, records and personal accounts to form the narrative of the implementation. A naturalist, intrinsic and multiple case study design utilising semi-structured interviews was used to consult with 27 Departmental staff and practitioners. Thematic analysis was utilised to identify key themes and patterns of experiences with the Signs of Safety framework implementation. Findings: Much can be learned from the journey of the Department and their long term commitment and systematic implementation strategy of Signs of Safety including the significance of leadership, learning and developing initiatives, effective communication, instituting continuous improvement processes and the provision of feedback for individual practitioners. Signs of Safety appealed to natural champions of systemic social work practise within the Department whose organisational culture adapted to align with the principles of the framework in building partnerships and understanding with families, being solution-focused, maintaining an open stance of inquiry and balancing strengths and safety around children whilst concurrently working to solve dangers and harm. As a learning organisation, the Department also utilised case practise implementation teams to be able to move through more successfully the different stages of implementation. In utilising Fixsen's implementation framework, the challenges and gaps to implementation strategies were also highlighted, including a problematic data system and an internal focus compromising the success of interagency collaboration. Conclusion: This discussion paper has provided an overview of the key concepts of the diffusion and implementation literature, and highlighted the importance of utilising theoretical frameworks in guiding implementation of practise models especially in complex statutory child protection contexts. Findings will be of particular interest to child welfare leaders and supporters of organisational change, providing concrete examples of implementation strategies and demonstrates the systemic benefits of a theoretical framework for guiding implementation efforts. Highlights: Importance of utilising theoretical frameworks for guiding implementation and change efforts Significance of leadership, learning initiatives and provision of feedback for individual practitioners as key facilitators Alignment of Signs of Safety ® framework and Departmental organisational culture in building partnerships with families Problematic data systems and interagency collaboration were identified as key challenges.